2018
DOI: 10.30630/joiv.2.4-2.178
|View full text |Cite
|
Sign up to set email alerts
|

Network Quality Assesment of Wireless Communication Based on Mobility Issue

Abstract: Up-gradation of wireless communication system is mainly based on some critical attributes like speed, coverage, interoperability, reliability, cost, security etc. This paper looks potential approaches to network quality analysis based on mobility. In this paper, focus is given to determine handover latency, vital property of mobility. This paper presents simulation to investigate handover effects-handover latency in homogeneous and heterogeneous environment using network simulator NCTUns 6.0 and simulator vers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The testing carried out in this research on system performance includes sensor reading response and network performance with several test scenarios made based on parameters such as latency on the network, QoS (Quality of Service) with parameters to be measured including bandwidth, delay, jitter and packet loss collected periodically from the publish subscribe scheme between sensor nodes [33]. When evaluating the quality of a network's data transfer, there are a number of characteristics that are typically considered.…”
Section: Testing Stagementioning
confidence: 99%
“…The testing carried out in this research on system performance includes sensor reading response and network performance with several test scenarios made based on parameters such as latency on the network, QoS (Quality of Service) with parameters to be measured including bandwidth, delay, jitter and packet loss collected periodically from the publish subscribe scheme between sensor nodes [33]. When evaluating the quality of a network's data transfer, there are a number of characteristics that are typically considered.…”
Section: Testing Stagementioning
confidence: 99%
“…It is shown that the efficiency of the IR-HARQ scheme depends on the choice of modulation and coding methods. In Mahjabeen et al [9], potential network quality analysis approaches based on mobility are researched. In Amali and Ramachandran [10], a broad survey on 5G cellular network architecture and some of the promising key technologies such as cloud RAN (Radio Access Network), Software-Defined Networking (SDN), Network Function Virtualization (NFV), and modulation formats are given.…”
Section: A Existing Workmentioning
confidence: 99%
“…The author in [32] employed an end-to-end mobility methodology which prescribes the use of control for user management, service management, and device control. A number of existing studies have examined the host identity protocol (HIP) to make a better mobility solution through several techniques such as: naming convention [33], using an ID between transport and network layer [34], robust path connection [35] and as a multi-path transmission [36].…”
Section: Related Workmentioning
confidence: 99%